Heavy Metal Pollution and Health Risk Assessment in Xiangjiang River Basin - WU Jialing; MAO Dehua (Renmin Zhujiang)
To study the level of heavy metal pollution in the Xiangjiang River Basin and its harm to human health,this paper selected the data from 26 monitoring stations in the whole basin from 2000 to 2016 and analyzed the temporal and spatial distribution characteristics of 7 heavy metals including Hg,Zn,Cu,As,Cr6+,Pb,and Cd.The pollution levels of these heavy metals were analyzed by the comprehensive pollution index evaluation method,and the health risk was preliminarily evaluated using the health risk evaluation model recommended by the US Environmental Protection Agency.Temporally,depending on the results of the comprehensive pollution index method and Mann-Kendall (MK) trend analysis,the water quality of the basin is in good condition and is improving year by year.Spatially,water quality in the upper reaches of the basin is better than that in the middle and lower reaches,and the high concentrations of heavy metals are mainly distributed in the middle and lower reaches.The health risk assessment results show that the average personal health risks of carcinogenic heavy metals in the basin are in the order of As>Cr6+>Cd,and the order of Pb>Cu>Zn>Hg is summed up for those of non-carcinogenic heavy metals.The basin is mainly affected by the risks of carcinogens.As and Cr6+ are the main sources of water health risks,and the health risks to children are much higher than to adults.